2014
DOI: 10.1121/1.4900170
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic-phonetic characteristics of older children’s spontaneous speech in interactions in conversational and clear speaking styles

Abstract: This study investigated (a) the acoustic-phonetic characteristics of spontaneous speech produced by talkers aged 9–14 years in an interactive (diapix) task with an interlocutor of the same age and gender (NB condition) and (b) the adaptations these talkers made to clarify their speech when speech intelligibility was artificially degraded for their interlocutor (VOC condition). Recordings were made for 96 child talkers (50 F, 46 M); the adult reference values came from the LUCID corpus recorded under the same c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…They observed higher word intensity for repeated words in FDS than NDS. Kendi and Khattab (2019), in their study on Arabic FDS, also reported significantly higher vowel intensity in FDS than NDS (in line with Hazan et al, 2015;cf. Knoll et al, 2015).…”
Section: Intensity and Pitchmentioning
confidence: 76%
See 3 more Smart Citations
“…They observed higher word intensity for repeated words in FDS than NDS. Kendi and Khattab (2019), in their study on Arabic FDS, also reported significantly higher vowel intensity in FDS than NDS (in line with Hazan et al, 2015;cf. Knoll et al, 2015).…”
Section: Intensity and Pitchmentioning
confidence: 76%
“…It is important to note that although some studies underscored the absence of heightened mean pitch in FDS, other studies have disclosed a different pattern of results. In recent work, Kendi and Khattab (2019) demonstrated that pitch average midpoints were higher in FDS than NDS (Hazan et al, 2015). However, this significant increase in mean pitch in FDS might be due to specific aspects of their study design.…”
Section: Rodriguezmentioning
confidence: 96%
See 2 more Smart Citations
“…Spontaneous conversational speech exhibits prosodic characteristics that distinguish it from read speech [3], e.g. syllabic reduction, decreased prosodic range [4] and differing stress placement [5]. Further, conversational turns are highly context-dependent, exhibiting changes in emotion and intent, topic/focus structure, and subtle prosodic changes due to phenomena such as (dis)entrainment.…”
Section: Introductionmentioning
confidence: 99%